Writing to your past-self can make you feel better - Sugimori, Eriko; Yamaguchi, Mayu; Kusumi, Takashi (Frontiers in Psychology, 2024)
Self-compassionate writing has been shown to be helpful for improving the mental state in some individuals. Here, we investigated how the writer’s attitude toward his/her past, present and future and the focus of the writing, i.e., social experience in the past versus self-experience, modulate these effects. In Experiment 1, 150 undergraduates wrote a compassionate letter to their past-self and to their future-self and responded to the Japanese version of the Adolescent Time Inventory–Time Attitudes (ATI-TA) questionnaire. Writing to past-self decreased negative feelings more than writing to future-self. Further, participants who had negative feelings toward their past, present, and future, as assessed by the ATI-TA, were more likely to be emotionally affected by writing a letter to their past-self. In Experiment 2, 31 undergraduates wrote a letter focusing on what they had experienced together with someone, and another 31 undergraduates wrote focusing on what they had experienced alone. Focusing on a social experience was more helpful for recovering from negative feelings than focusing on a self-experience. In conclusion, writing a compassionate letter to one’s past-self can improve mood, especially in individuals with a negative time attitude who focus their writing on a social connection.